The Gen Z frequency : how brands tune in and build credibility - Witt, Gregg L., ....-; Baird, Derek E., ....- (London : Kogan Page, 2018)
Generation Z, ranging from tweens to young adults, has enormous spending power; yet it is one of the most challenging generational cohorts for brands to reach. It is projected to be the largest consumer demographic in history, driving a forecast from the HRC Retail Advisory of 40% of all US consumer spending, and another 40% of all consumers in the US, Europe and BRIC by 2020 (Brazil, Russia, India, China), according to other sources. Embodying an unrelenting relationship with information and mobile technology from a young age, Generation Z's ecosystem is infinitely more complex and varied than any generation before. Staying tuned-in to this demographic's impatience, confidence and constantly evolving trends can be daunting for any marketer trying to keep up. The Gen Z Frequency offers a comprehensive guide for any brand or organization trying to reach this demographic, covering fundamental truths, content creation, engagement strategies and tactics such as social media, experiential, emerging technologies, and much more. It is woven with fascinating case studies and real-world stories from the trenches, plus key insights from leading youth brands and Gen Z themselves. Whether you are new to marketing or a seasoned expert, The Gen Z Frequency is the ultimate resource for tuning in to Generation Z.
Includes bibliographical references and index.
Keywords: Branding (Marketing).; Consumer behavior; Consumers' preferences; Generatie Z